Visual agnosia and Kluver-Bucy syndrome in marmosets (Callithrix jacchus) following ablation of inferotemporal cortex, with additional mnemonic effects of immunotoxic lesions of cholinergic projections to medial temporal areas. - Ridley, R; Warner, K; Maclean, C; Gaffan, D; Baker, H (2001)
Inferotemporal ablations in the New World monkey, the common marmoset (Callithrix jacchus), produced a persistent impairment on visual discrimination learning and a florid, but transient, Klüver-Bucy syndrome. Monkeys with these ablations were impaired on acquisition of object discriminations to a high criterion and on concurrent discrimination learning, to a single high criterion across all trials. Neither the control monkeys nor the monkeys with inferotemporal ablations found acquisition more difficult when the component discriminations of a set were presented concurrently compared to consecutively, although the monkeys with inferotemporal ablations found acquisition under both these conditions somewhat more difficult than did control monkeys. This suggests that the severe impairment caused by inferotemporal ablations on concurrent learning measured across all trials is due to the need for sustained performance across a concurrent set rather than to the extra mnemonic demands of concurrent presentation. When immunotoxic lesions of the cholinergic projection to the hippocampal formation were added to the inferotemporal ablations, a further impairment on retention, and a differential impairment on concurrent, compared to consecutive, learning was observed. Previous studies have shown that lesions of the cholinergic projection to the hippocampus alone, or excitotoxic hippocampal lesions, do not affect simple visual discrimination learning. It is suggested that large inferotemporal ablations in monkeys produce a visual agnosia which causes severe 'psychic blindness' in the first instance, and a persistent impairment on visual discrimination learning. The hippocampus makes a contribution, which may be mnemonic, to discrimination performance after inferotemporal ablations.